NF-κB, neutrophil extracellular traps, and microglial in mice with Streptococcus suis serotype 2 meningitis infection - Susilawathi, Ni Made; Adi Tarini, Ni Made; Arijana, I Gusti Kamasan Nyoman; Sriwidyani, Ni Putu; Pramitasuri, Tjokorda Istri; Sudewi, Anak Agung Raka; Mahardika, I Gusti Ngurah Kade (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Streptococcus suis is the most frequent etiology of zoonotic bacterial meningitis, potentially initiating an outbreak. Acute bacterial meningitis caused by S. suis has various manifestations, often accompanied by sepsis with multiple organ involvement. This study aimed to evaluate the pattern of S. suis outgrowth in the brain, which is associated with nuclear factor-κappaB (NF-κB) activation, neutrophil extracellular traps (NETs) release (NETosis), and microglial activation as three crucial pathological mechanisms of bacterial meningitis. METHODS This study used 64 female BALB/c mice aged 6 weeks and weighed 18−20 g, grouped into infected and non-infected as the control group. Both groups were administered 1 ml of S. suis serotype 2 suspension (1 × 107 colony forming-unit/ml) and normal saline intraperitoneally. The bacterial colony count of S. suis was evaluated, along with NF-κB and NET levels in blood and brain, as well as meningeal inflammation and microglial activation in the brain at Days 1, 3, 5, and 7 post-infection. RESULTS The invasion of S. suis into the brain slightly induced NF-κB activation, leading to a burst of inflammatory responses, neutrophil infiltration with NET releases, and microglia activation that co-occurred, showing their peaks on Days 3 and 5 after onset. CONCLUSIONS The S. suis invasion into the mice’s brain increased NF-κB activation, NETosis, and microglia activation during S. suis meningitis infection.